2019
DOI: 10.14202/vetworld.2019.1175-1179
|View full text |Cite
|
Sign up to set email alerts
|

Detection of parasitic helminths in cattle from Banda Aceh, Indonesia

Abstract: Aim: The objective of this research was to identify the parasite species found in the gastrointestinal tract and pancreas of Aceh cattle slaughtered in a Banda Aceh slaughterhouse using lactophenol and semichon carmine staining. Materials and Methods: Each sample out of 50 samples of gastrointestinal tract and pancreas from Aceh cattle slaughtered in a Banda Aceh slaughterhouse was separated by organ. Each organ was examined for the presence of worm. Then, the parasitic worms found were subsequently collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…The prevalence of E. pancreaticum was detected in Aceh cattle with a prevalence rate of 0.4% (Hanafiah et al 2019). Lucca et al (2015) mentions that the prevalence of E. pancreaticum in cattle may occur, in extreme cases up to 100%, while (Okajima et al 2016) reported that the prevalence of eurytrematiasis was less than 1% in animal slaughterhouses in Japan.…”
Section: Morphology Observation By Worm Stainingmentioning
confidence: 99%
“…The prevalence of E. pancreaticum was detected in Aceh cattle with a prevalence rate of 0.4% (Hanafiah et al 2019). Lucca et al (2015) mentions that the prevalence of E. pancreaticum in cattle may occur, in extreme cases up to 100%, while (Okajima et al 2016) reported that the prevalence of eurytrematiasis was less than 1% in animal slaughterhouses in Japan.…”
Section: Morphology Observation By Worm Stainingmentioning
confidence: 99%
“…Adults T. spiralis were also divided into two different groups; group IIa to be mounted with glycerol jelly and group IIb to be stained and mounted with LMB-BGJ, respectively. Carmine stain was not preferred for T. spiralis owing to the thick cuticle that prevents the stain to be absorbed into this layer and the visceral organs as well [10] . The structural brightness and the extent of staining of different parts of the samples were scored.…”
Section: Methodsmentioning
confidence: 99%
“…Kondisi ini menyebabkan gangguan kesehatan bahkan kematian pada hewan jika tidak segera ditangani (Rinaldi et al, 2009;McManus et al, 2014;Malathi et al, 2021). Disamping itu terdapat juga spesies Trematoda lain yang ditemukan menginfeksi ruminansia besar di Indonesia diantaranya Eurytrema pancreaticum (Hanafiah et al, 2019) dan Schistosoma japonicum (Budiono et al, 2018) Badan Pusat Statistik Kabupaten Sumba Timur melaporkan penurunan populasi kerbau yang signifikan pada tahun 2020. Populasi kerbau pada tahun 2020 tercatat sebesar 33.659 ekor dari tahun sebelumnya yang berjumlah 39.821 ekor (BPS Kabupaten Sumba Timur, 2021).…”
Section: Pendahuluanunclassified